Determination of the motor types of younger children by classification into groups - Planinšec, Jurij (Kinesiologia Slovenica, 2001)
The purpose of the present study is to determine the motor types of younger children and find out the most important characteristics of the individual motor types. The children were 138 girls and 125 boys 5 years age, from the city of Maribor and its surroundings. For the assessment of motor abilities twentyeight tests were used. Ward's hierarchical method was used for the classification of children into groups. Both genders have achieved similar results. On the basis of these results we conclude that for boys and girls there are three groups with the following characteristics: a) above-average general motor efficiency, c) below average general motor efficiency, b) average general motor efficiency. For 5 year-old children it is primarily the general motor ability, defined by the informational and energy components of movement, which has the most influence on the prevailing motor types. Results obtained in this way could help us to plan a transformational process within the framework of the sports activities, which is adapted to the needs of individual groups of children
Keywords: motorične sposobnosti; predšolski otroci; raziskave; razvrščanje v skupine